2016
DOI: 10.1177/1352458516663034
|View full text |Cite
|
Sign up to set email alerts
|

Association of asymptomatic spinal cord lesions and atrophy with disability 5 years after a clinically isolated syndrome

Abstract: Attempts at improving physical activity rates among the population are central to many government, public health, and third sector approaches to encouraging health behaviours. However, to date there has been little attempt by public health to embrace different theoretical-methodological approaches, relying instead upon largely quantitative techniques. This paper argues that through a development of a framework of affect amplification, public health approaches to physical activity should incorporate the choreog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
3
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(143 citation statements)
references
References 56 publications
(106 reference statements)
8
125
3
4
Order By: Relevance
“…The rates of spinal cord loss over 1 year obtained with GBSI were similar to those obtained with CSA, but they were associated with lower variability, greater ability to distinguish between MS patients and controls, and more robust clinical correlates, thereby holding promise for future MS research on spinal cord imaging. [3][4][5] Spinal cord atrophy occurs from the early stages of MS (eg, CIS), is more obvious in progressive patients than relapsing types of MS, and progresses faster than brain atrophy. CSA and GBSI provided similar rates of spinal cord atrophy in each MS subtype, but CSA yielded a larger variability (standard deviation) when compared with GBSI (eg, in RRMS AE4.02% vs AE2.57%, respectively), implying that GBSI measurements are more precise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of spinal cord loss over 1 year obtained with GBSI were similar to those obtained with CSA, but they were associated with lower variability, greater ability to distinguish between MS patients and controls, and more robust clinical correlates, thereby holding promise for future MS research on spinal cord imaging. [3][4][5] Spinal cord atrophy occurs from the early stages of MS (eg, CIS), is more obvious in progressive patients than relapsing types of MS, and progresses faster than brain atrophy. CSA and GBSI provided similar rates of spinal cord atrophy in each MS subtype, but CSA yielded a larger variability (standard deviation) when compared with GBSI (eg, in RRMS AE4.02% vs AE2.57%, respectively), implying that GBSI measurements are more precise.…”
Section: Discussionmentioning
confidence: 99%
“…3,18,[24][25][26] Eligibility criteria were (1) diagnosis of clinically isolated syndrome or MS according to the 2010 McDonald Criteria 27 ; Overall, we included 327 MS patients and 96 healthy controls.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Briefly, patients were initially recruited into the study within 3 months of a CIS and invited to return for scheduled clinical and MRI follow-up, irrespective of clinical status 12. The clinical and MRI assessments presented here were done ~15 years after CIS.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies, quantifying cord lesions, have found that especially cervical lesions were associated with disability in both relapsing and progressive forms of MS and a higher lesion load was seen in patients with progressive MS. 60 As in RIS, spinal lesions are predictive of developing clinically definite MS from CIS, wherein two thirds of patients with initial nonspinal CIS, having concomitant spinal cord lesions, developed MS after 5 years. 50 T1-hypointense lesions T1-hypointense lesions, so-called 'black holes', are hypointensities that are persistent for 6 months after the initial enhancement 61 and show significant demyelination and axonal loss. 62 Chronic T1-hypointense lesions are closely linked to neurodegeneration and are known to correlate with disability in patients with MS. 63 There is increased interest in the predictive value of T1-hypointense lesions, which are utilized more often as an endpoint for clinical studies.…”
Section: T2-hyperintense Lesionsmentioning
confidence: 99%